Diagnostic Approach in Infants and Children with Mitochondrial Diseases - Ching-Shiang Chi (Elsevier, 2015)
Mitochondrial diseases are a heterogeneous group of disorders affecting energy production in the human body. The diagnosis of mitochondrial diseases represents a challenge to clinicians, especially for pediatric cases, which show enormous variation in clinical presentations, as well as biochemical and genetic complexity. Different consensus diagnostic criteria for mitochondrial diseases in infants and children are available. The lack of standardized diagnostic criteria poses difficulties in evaluating diagnostic methodologies. Even though there are many diagnostic tools, none of them are sensitive enough to make a confirmative diagnosis without being used in combination with other tools. The current approach to diagnosing and classifying mitochondrial diseases incorporates clinical, biochemical, neuroradiological findings, and histological criteria, as well as DNA-based molecular diagnostic testing. The confirmation or exclusion of mitochondrial diseases remains a challenge in clinical practice, especially in cases with nonspecific clinical phenotypes. Therefore, follow-up evolution of clinical symptoms/signs and biochemical data is crucial. The purpose of this study is to review the molecular classification scheme and associated phenotypes in infants and children with mitochondrial diseases, in addition to providing an overview of the basic biochemical reactions and genetic characteristics in the mitochondrion, clinical manifestations, and diagnostic methods. A diagnostic algorithm for identifying mitochondrial disorders in pediatric neurology patients is proposed.